Addition of interleukin‐6 receptor blockade to carfilzomib‐based desensitization in a highly sensitized nonhuman primate model. (1st December 2022) - Anwar, Imran J.; Ezekian, Brian; DeLaura, Isabel; Manook, Miriam; Schroder, Paul; Yoon, Janghoon; Curfman, Verna; Branum, Evelyn; Messina, Julia; Harnois, Melissa; Permar, Sallie R.; Farris, Alton B.; et al.
Abstract : Sensitized patients, those who had prior exposure to foreign human leukocyte antigens, are transplanted at lower rates due to challenges in finding suitable organs. Desensitization strategies have permitted highly sensitized patients to undergo kidney transplantation, albeit with higher rates of rejection. This study assesses targeting plasma cell and interleukin (IL)‐6 receptor for desensitization in a sensitized nonhuman primate kidney transplantation model. All animals were sensitized using two sequential skin transplants from maximally major histocompatibility complex‐mismatched donors. Carfilzomib (CFZ)/tocilizumab (TCZ) desensitization ( N  = 6) successfully decreased donor‐specific antibody (DSA) titers and prevented the expansion of B cells compared to CFZ monotherapy ( N  = 3). Dual desensitization further delayed, but did not prevent humoral rebound, as evidenced by a delayed increase in post–kidney transplant DSA titers. Accordingly, CFZ/TCZ desensitization conferred a significant survival advantage over CFZ monotherapy. A trend toward increased T follicular helper cells was also observed in the dual therapy group along the same timeline as an increase in DSA and subsequent graft loss. Cytomegalovirus reactivation also occurred in the CFZ/TCZ group but was prevented with ganciclovir prophylaxis. In accordance with prior studies of CFZ‐based dual desensitization strategies, the addition of IL‐6 receptor blockade resulted in desensitization with further suppression of posttransplant humoral response compared to CFZ monotherapy. Graphical Abstract: Addition of IL‐6R blockade to carfilzomib‐based desensitization prolongs allograft survival but does not prevent the posttransplant humoral response in a highly sensitized nonhuman primate model.